Bilateral paramedian midbrain infarct: an uncommon variant of the "top of the basilar" syndrome. Issue 5 (15th April 2005) - Spengos, K; Wohrle, J C; Tsivgoulis, G; Stouraitis, G; Vemmos, K; Zis, V
Abstract : Occlusion of the rostral portion of the basilar artery can result in ischaemia of the midbrain and thalami, as well as of the temporal and occipital lobes. The so called "top of the basilar" syndrome manifests clinically as numerous combinations of abnormalities of alertness, sleep–wake cycle, and behaviour and oculomotor or pupillomotor functions. A 67 year old man presented with bilateral internuclear ophthalmoplegia, rubral tremor, and daytime somnolence. He was awake during the night and mostly agitated and aggressive. An ischaemic lesion was visible on the magnetic resonance (MR) image in the central portion of the midbrain just ventral to the aqueduct, clearly affecting the paramedian structures bilaterally. MR angiographic images demonstrated a hypoplastic basilar artery ending in both superior cerebellar arteries. Both posterior cerebral arteries were seen to arise from the corresponding internal carotid arteries via the posterior communicating branches. This unique case of an acute bilateral paramedian infarct represents a highly uncommon variant of the "top of the basilar" syndrome and was due to the affected ischaemic territory—that is, the "distal field" of the variant basilar artery.